Building responsive and responsible financial regulators in the aftermath of the global financial crisis / editor, Pablo Iglesias-Rodríguez. - Iglesias-Rodríguez, Pablo (Intersentia, 2015)
The global financial crisis that started in 2007 sparked several academic debates about the role that financial sector regulators played in the crisis and prompted policy reforms in the financial supervision architectures of several countries. This book focuses on the question of what accountability, independence, transparency and, more generally, governance mechanisms applicable to financial regulators can better contribute to building responsive, responsible and effective regulatory and supervisory frameworks that tackle the weaknesses of the pre-crisis regimes. It re-visits the concepts of accountability and independence of financial regulators as well as the main economic theories underlying financial services policy-making, in light of the crisis experience. In addition, it critically examines the post-crisis institutional frameworks of financial regulation and supervision in the EU, the US and Canada with a view to assessing whether the financial regulators of the post-global financial crisis era are well suited to effectively address the challenges and threats that global financial markets pose to the stability, integrity and good functioning of financial systems as well as to the protection of consumers, investors and society at large.Topics addressed in this volume include:- The theoretical foundations of accountability and independence in financial regulation after the crisis; - The influence of economic theory on the quality of financial regulation and supervision;- Accountability in the European Banking Union and the European System of Financial Supervision;- Post-crisis structures of financial regulation in the US and their impact on consumer/investor protection and financial stability;- The role of financial supervision architecture in the stability of the Canadian financial system. The contributors to this volume are economists, lawyers, political scientists and sociologists from both academia and practice. Therefore, this book will be highly relevant to scholars and practitioners in these areas.